From an elongated cavity to funnel by the impact of a drop train. (25th August 2021) - Lee, Jae Hong; Kim, Seungho; Kim, Joonoh; Kim, Hyoungsoo; Kim, Ho-Young
Abstract: Abstract : The impact of a drop train, a series of identical liquid drops separated by a constant distance, on a liquid pool initially generates a long slender cavity. However, the cavity soon collapses and turns into a shallow funnel. Here we theoretically model the dynamic profile of the elongated cavity and the steady shape of the funnel, which are then shown to agree well with experiment. When the liquid inertia plays a dominant role, the cavity assumes a parabolic profile that depends only on the drop diameter and the centre-to-centre spacing of adjacent drops. We consider the capillary forces as well as the drop impact force to obtain the shape of the funnel that persists once the elongated cavity collapses. Our study allows for predicting the interfacial morphology by the impact of a drop train and designing impact conditions useful for semiconductor cleaning processes.